1989
DOI: 10.1128/mcb.9.1.252
|View full text |Cite
|
Sign up to set email alerts
|

Role of arachidonic acid metabolism in transcriptional induction of tumor necrosis factor gene expression by phorbol ester.

Abstract: The treatment of human HL-60 promyelocytic leukemia cells with 12-O-tetradecanoylphorbol-13-acetate (TPA) is associated with induction of tumor necrosis factor (TNF) transcripts. The study reported here has examined TPA-induced signaling mechanisms responsible for the regulation of TNF gene expression in these cells. Run-on assays demonstrated that TPA increases TNF mRNA levels by transcriptional activation of this gene. The induction of TNF transcripts by TPA was inhibited by the isoquinolinesulfonamide deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 48 publications
6
42
0
Order By: Relevance
“…Furthermore, preincubation with TPA to downregulate protein kinase C also abolished the response of x rays (34). Together with the results demonstrating the induction of TNF gene expression by phorbol esters (20,28), these findings suggest that the effects of ionizing radiation on TNF gene expression might also be mediated by a protein kinase C-dependent mechanism.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, preincubation with TPA to downregulate protein kinase C also abolished the response of x rays (34). Together with the results demonstrating the induction of TNF gene expression by phorbol esters (20,28), these findings suggest that the effects of ionizing radiation on TNF gene expression might also be mediated by a protein kinase C-dependent mechanism.…”
Section: Resultssupporting
confidence: 67%
“…TNF is actively transcribed in thioglycollate-elicited peritoneal macrophages, while an increase in the rate of TNF transcription was observed after treatment with LPS or interferon-y (26,27). We have previously demonstrated that TNF induction by 12-tetradecanoylphorbol-13-acetate (TPA)' is regulated by transcriptional mechanisms in human peripheral blood monocytes as well as in myeloid leukemia cell lines (20,28). In order to determine the level of regulation ofTNF gene expression by ionizing radiation, we first measured the rate ofTNF transcription in isolated nuclei using the run-on transcription assay method.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these results indicated that M-CSF regulates EGR-I gene expression in monocytes by both transcriptional and posttranscriptional mechanisms, whereas EGR-2 expression is regulated at least in part by a posttranscriptional mechanism in these cells. We have previously demonstrated that glucocorticoids inhibit induction of monocytic differentiation (20)(21)(22). Consequently, we treated TPA-induced U-937 cells with dexamethasone to determine the effects of this agent on EGR-l gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…(10)(11)(12)(13)(14)(15)(16). Previous studies have demonstrated that the c-jun, jun-B, and c-fos genes are activated during TPA-induced monocytic differentiation (7,(17)(18)(19)(20). Moreover, the finding that pretreatment with dexamethasone inhibits expression of these genes, as well as TPA-or dimethyl sulfoxide (DMSO)-induced monocytic differentiation, has implicated a role for Jun/ AP-l in this process (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LTB4 was found to modulate the production of cytokines by monocytes (Rola-Pleszczinski & Lemaire, 1985; 'Author for correspondence. Horiguchi et al, 1989;Rola-Pleszczinski & Stankova, 1992) and the proliferation of lymphocytes (Payan et al, 1984;Gualde et al, 1985;Atluru & Goodwin, 1986;Yamaoka et al, 1989). The recent development of LTB4 antagonists and inhibitors of 5-lipoxygenase have outlined a role for this lipid mediator in acute inflammatory states such as in endotoxic shock (Matera et al, 1988;Fujimoto & Kobayashi, 1988;Coggeshall et al, 1988;Yoshikawa & Goto, 1992).…”
Section: Introductionmentioning
confidence: 99%